The Influence of Gender, Financial Literacy, and Financial Technology on Financial Management of Management Students of The 2021 Class, University of Tribhuwana Tunggadewi, Malang - Rizki Aprilia Dwi Susanti; Moh. Askiyanto; Muhim Matur Rosidah (International Research & Development for Human Beings (IRDH), 2026)
This study aims to determine the influence of gender, financial literacy, and financial technology on financial management in college students. This research uses a quantitative approach, focusing on hypothesis testing with statistical analysis tools and producing generalizable conclusions. The sample in this study was Management students from the 2021 intake of Tribhuwana Tunggadewi University, Malang. The test tool used was multiple linear regression analysis with SPSS 26 software. Data were collected through a questionnaire that included questions about gender, financial literacy, financial technology, and financial management. The results of this study indicate that gender, financial literacy, and financial technology have a positive and significant influence on student financial management. Good gender, financial literacy, and financial technology can help students achieve their financial goals and prevent financial problems.